PERAN PSIKOLOGI AGAMA ISLAM TERHADAP KESEHATAN MENTAL ANAK REMAJA - mitha shaskila sinaga (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
This study aims to analyze the role of Islamic religious psychology on the mental health of adolescents. The focus of the study is on three things, namely religion and mental health, mental health disorders and the role of the psychology of religion in adolescent mental health. This study analyzes the role of religious psychology on adolescent mental health. This research method uses a literature study approach or library research based on descriptive studies. The data collection technique used is to choose a topic and seek information from various sources, namely: books, journals, mass media, etc. The data obtained was then analyzed using the Miles and Huberman technique, namely collecting data, coding to make the analysis process easier, and drawing conclusions. The results of the study explain that the important role of the psychology of religion in the mental health of adolescents, especially adolescents who experience mental health disorders. With the psychology of religion, it can minimize the phenomena that often occur in adolescent mental health.Â Keywords: Mental health, Adolescents, The role of the psychology of religion